Miscommunication amongst Persian learners of English as a foreign language / Nastaran Zahra Bodaghi - Bodaghi, Nastaran Zahra (2013)
This study examines miscommunication faced by Iranians when they use their English knowledge in a foreign country like Malaysia and to recommend ways to overcome the problem. To investigate miscommunications that Iranians face in their real interactions, 12 Iranians who are postgraduate students in Malaysia are asked to describe their experiences of miscommunications. These Iranians had learnt English in Iran, which can be considered as either an EFL or EIL country, and later lived in Malaysia, an ESL country. The analysis of the study reveals two major sources of miscommunications, language and culture. Culture contributed 64% while language 36% towards the sources of miscommunication. Thus, culture made up about 2/3 of the sources of miscommunication between the Iranians and Malaysians of the study. Regarding language, there are four minor categories that contributed to language being a source of miscommunication. They are differing accent, low standard of English of Malaysians and Iranians, use of Manglish and the lack of English language knowledge. Three minor categories are identified as factors that contributed towards culture being a source of miscommunication. They are differing temperament and habits, differing expectations and different meanings accorded to body language. With regard to how Iranians can overcome the problems in cross cultural communication, it is recommended that Iranians have a good proficiency in English, know a bit of Malay and have some knowledge of Malaysian culture. The implications of the study indicate that the knowledge of cultural behavior reduces miscommunications. Also the respondents clarified that each variety of English is bound closely to the sociolinguistic conventions of its users. Therefore, if the goal is better communication, teachers should not only rely on classroom materials such as textbooks, but also to look for more authentic sources of information in real-life communication break-downs and their possible reasons to enable learners to avoid cross-cultural misunderstandings in communication in the English language.